Genome analysis of Actinobacillus pleuropneumoniae strain APPFJLYC01 reveals multidrug resistance and high virulence potential - Zhihong Fang; Zecheng Lin; Chuchu Duan; Xiaojin Liu; Zhongfeng Luo; Cuiqin Huang; Xiaohua Li; Xintian Zheng (PLoS ONE, 2025)
Actinobacillus pleuropneumoniae is the primary etiological agent of porcine contagious pleuropneumonia, a devastating respiratory disease that causes substantial economic losses to the global swine industry. The emergence of multidrug-resistant strains with enhanced virulence poses increasing challenges to disease control and necessitates comprehensive genomic characterization to inform targeted intervention strategies. This study aimed to characterize the genomic features, antimicrobial resistance profile, and pathogenic potential of a novel A. pleuropneumoniae strain isolated from a severe outbreak in China, with particular focus on identifying unique resistance mechanisms and virulence determinants. We isolated strain APPFJLYC01 from lung and bronchial tissues of pigs during a severe pleuropneumonia outbreak in Fujian Province, China (incidence rate 30%, mortality rate 56%). Complete genome sequencing was performed using combined PacBio Sequel II and DNBSEQ platforms, followed by comprehensive bioinformatics analysis including virulence factor identification, antibiotic resistance gene profiling, phylogenetic analysis, and comparative genomics. Pathogenicity was evaluated through experimental infection of 3-week-old piglets with subsequent clinical, pathological, and histopathological examinations. The genome of APPFJLYC01 strain is 2,308,741 bp in size, encoding 2,149 genes. Notably, it contains 190 virulence factor homologs and 10 resistance genes. Phylogenetic analysis based on CorePan revealed that APPFJLYC01 shares a close evolutionary relationship with strain JL03, potentially due to their shared geographical origin in China. Pathogenicity evaluation in piglets confirms its high virulence. These findings highlight APPFJLYC01 as a multidrug-resistant and highly virulent strain, providing insights for controlling porcine pleuropneumonia.